2009
DOI: 10.1097/bcr.0b013e318191fc91
|View full text |Cite
|
Sign up to set email alerts
|

Demographics of Pediatric Burns in Vellore, India

Abstract: The American Burn Association, Children's Burn Foundation, and Christian Medical College in Vellore, India have partnered together to improve pediatric burn care in Southern India. We report the demographics and outcomes of burns in this center, and create a benchmark to measure the effect of the partnership. A comparison to the National Burn Repository is made to allow for generalization and assessment to other burn centers, and to control for known confounders such as burn size, age, and mechanism. Charts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…In the series considering scaldings that are sub-titled, some differences evolve in the clinical course and outcomes of the patients; however, previous reports regarding such subgroups of scalding and the number of the patients studied are limited. [3] In our study, according to our literature search, we present the largest series on scalding comparing hot water and other concentrated liquids. To evaluate the outcomes of different concentrated liquid burns in children, we prospectively followed up the burned pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the series considering scaldings that are sub-titled, some differences evolve in the clinical course and outcomes of the patients; however, previous reports regarding such subgroups of scalding and the number of the patients studied are limited. [3] In our study, according to our literature search, we present the largest series on scalding comparing hot water and other concentrated liquids. To evaluate the outcomes of different concentrated liquid burns in children, we prospectively followed up the burned pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…Milk burns have significantly higher mortality risk than other scalds. [3] In conclusion, scalding is the most frequent burn cause among the Turkish pediatric population. Hot milk burns should be considered as an important entity among scalds as they have a complicated clinical course and considerable mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…To be less able to perceive danger, have less control over their environment and to react slower in situations that can lead to injury, occasionally make the injury unavoidable in small children. [16] As shown in our study, childhood scalding injury is frequently observed among the preschool period, especially between the ages of 2 and 3 years [1][2][3][5][6][7][17][18][19] in which the abilities that increased tendency to injuries were gained such as independent mobility, exploratory behavior, and hand-to-mouth activity. [20,21] Similar to the previous studies from Turkey [23,25] the mechanism of hot milk burns was most commonly the immersion and most frequently affected anatomical parts were the lower extremities and the trunk.…”
Section: Number Of Patients Mean Burned Bsa (%) Mortality Rate (%)mentioning
confidence: 99%
“…It requires a treatment process including a multidisciplinary approach by experienced burn surgeons and health care professionals in a well-equipped burn unit or center. Majority of burns among the pediatric patients was caused by scalding in both developed [1,2] and developing countries, [3,4] as well as in Turkey. [5][6][7] Particularly, this trauma is frequently observed among the children that belonged to joints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation